Epidemiology of monkeypox notifications in the state of Minas Gerais, Brazil - Paula Luciana Gonçalves Pereira; Edmundo Rinolino Magalhães Flores; Thales Philipe Rodrigues da Silva; Ana Paula Vieira Faria; Elice Eliane Nobre Ribeiro; Ana Paula Sayuri Sato; Larissa Pereira Gomes; Fernanda Penido Matozinhos (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to describe the epidemiological profile of suspected, confirmed, and probable cases of monkeypox in the state of Minas Gerais, Brazil. Methods: a descriptive, retrospective study of reported suspected, confirmed, and probable cases of monkeypox infection in the state of Minas Gerais, Brazil. The study period was from the first notification, on June 11, to September 7, 2022. Results: a total of 759 suspected, confirmed, and probable cases of monkeypox infection were reported, with 35.44% suspected, 53.75% confirmed, and 10.81% probable cases, respectively. As for the coexisting diseases within confirmed cases, 38.79% were related to people living with human immunodeficiency virus, and 13.74% had some active sexually transmitted infection. Regarding the evolution of confirmed cases, 47.43% were cured. Conclusions: the results contribute to greater knowledge and control of the infection by allowing better disease management and care offered in health services.